2021
DOI: 10.3390/children8020099
|View full text |Cite
|
Sign up to set email alerts
|

Experience and Prevalence of Dental Caries in 6 to 12-Year-Old School Children in an Agricultural Community: A Cross-Sectional Study

Abstract: Objective: To describe the experience and prevalence of dental caries in schoolchildren aged 6–12 years belonging to agricultural manual worker households. Material and Methods: A comparative cross-sectional study was conducted in two groups of schoolchildren: One considered “children of agricultural worker migrant parents” (n = 157) and the other “children of agricultural worker non-migrant parents” (n = 164). Epidemiological indices for dental caries were calculated for primary (dmft) and permanent (DMFT) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
2
6
2
Order By: Relevance
“…The noted prevalence of dental caries among the children studied herein corroborates other studies from Thailand 9 and internationally; 10,11 although, its cross-sectional design does not allow us to make any inferences about whether the prevalence is decreasing locally, as seen globally. 12,13 However, the findings of our study seem to be a bit higher for DMFT and a bit lower for dmft in comparison to other studies.…”
Section: Discussionsupporting
confidence: 84%
“…The noted prevalence of dental caries among the children studied herein corroborates other studies from Thailand 9 and internationally; 10,11 although, its cross-sectional design does not allow us to make any inferences about whether the prevalence is decreasing locally, as seen globally. 12,13 However, the findings of our study seem to be a bit higher for DMFT and a bit lower for dmft in comparison to other studies.…”
Section: Discussionsupporting
confidence: 84%
“…While in Latin America there is only a small number of countries that report dental health status with nationally representative samples [2], dental caries is the most prevalent oral disease [3]. In Mexico, the situation is similar, with low utilization of preventive dental services and high prevalence of caries and treatment needs in children and adolescents [4][5][6][7][8][9][10]. In general, about half of individuals between 6 and 12 years of age present caries lesions in any tooth of either primary or permanent dentition [4,10], with consequences in terms of pain, suffering, functional impairment, and reduced quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, the situation is similar, with low utilization of preventive dental services and high prevalence of caries and treatment needs in children and adolescents [4][5][6][7][8][9][10]. In general, about half of individuals between 6 and 12 years of age present caries lesions in any tooth of either primary or permanent dentition [4,10], with consequences in terms of pain, suffering, functional impairment, and reduced quality of life. Access to oral care is limited in many developing countries; teeth are often left untreated or extracted [3,4,6,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study from Mexico demonstrated that over half of 6-12-year-old school children from agricultural manual worker households had caries in either or both dentitions, and a considerable proportion were untreated lesions. However, the authors noted that the prevalence levels in their study were lower than other reports from Mexico in similar age groups [5]. Another paper from Mexico quantified the association between self-reported dental caries and socioeconomic indicators in a national sample of Mexican children.…”
mentioning
confidence: 69%